2015
DOI: 10.1021/acs.est.5b04826
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Phenolic Antioxidants and Their Metabolites in Indoor Dust from Homes and Microenvironments

Abstract: Synthetic phenolic antioxidants (SPAs), including 2,6-di-tert-butyl-4-hydroxytoluene (BHT), are extensively used in food, cosmetic and plastic industries. Nevertheless, limited information is available on human exposures, other than the dietary sources, to SPAs. In this study, occurrence of 9 SPAs and their metabolites/degradation products was determined in 339 indoor dust collected from 12 countries. BHT was found in 99.5% of indoor dust samples from homes and microenvironments at concentrations that ranged f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
86
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(98 citation statements)
references
References 26 publications
10
86
2
Order By: Relevance
“…High detection frequencies were found for BHA in urban (89%) and rural dust samples (100%) in this study with GM concentrations of 12.0 ng/g and 84.0 ng/g, respectively. While, one previous study showed that, for the dust samples collected from 12 countries, BHA was exclusively in samples from China (Wang et al, 2016). Sporadic studies were found reporting the occurrence of 4-tOP in settled house dust matrix from China with median concentration of 80.0 ng/g (Lu et al, 2013).…”
Section: Spa Concentrations and Composition Profiles In Dust Samplesmentioning
confidence: 94%
See 1 more Smart Citation
“…High detection frequencies were found for BHA in urban (89%) and rural dust samples (100%) in this study with GM concentrations of 12.0 ng/g and 84.0 ng/g, respectively. While, one previous study showed that, for the dust samples collected from 12 countries, BHA was exclusively in samples from China (Wang et al, 2016). Sporadic studies were found reporting the occurrence of 4-tOP in settled house dust matrix from China with median concentration of 80.0 ng/g (Lu et al, 2013).…”
Section: Spa Concentrations and Composition Profiles In Dust Samplesmentioning
confidence: 94%
“…Among the SPA analytes, BHT was detectable in all of the investigated urban (n ¼ 55) and rural dust samples (n ¼ 20) with concentrations of 852e1.84e4 ng/g (GM: 2.27e3 ng/g) and 163e2.33e3 ng/g (GM: 773 ng/g), respectively. Limited studies showed that BHT existed in dust samples with concentrations from 170 ng/g to 7.00e4 ng/g (Nilsson et al, 2005;Wang et al, 2016). High concentrations of BHT (230e1.30e3 ng/g) were also reported in human body fat in UK and USA (Collings and Sharratt, 1970), though no study investigated the relationship between the BHT occurrence in human body and its exposure through dust ingestion.…”
Section: Spa Concentrations and Composition Profiles In Dust Samplesmentioning
confidence: 99%
“…BHA and BHT have already been found to be responsible for adverse effects on the liver and for carcinogenesis in animal studies [19,33]. Additionally, very little is known about the environmental occurrence and fate of these compounds [37,38]. The tendency to replace these antioxidants with natural ones has been increasing [39].…”
Section: Replacing Synthetic Antioxidants With Natural Antioxidantsmentioning
confidence: 99%
“…[8]. A recent study indicated presence of antioxidant gallic acid esters (gallates) in dust from homes and microenvironments [9].…”
Section: Introductionmentioning
confidence: 99%